2015
DOI: 10.15713/ins.jmrps.28
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma: A 5 years institutional study

Abstract: Background: Oral squamous cell carcinoma (OSCC) is a major contributor to disability and death caused by malignant tumors. While of global relevance, variations in social, cultural, and geographic factors affect tumor behavior and response to treatment. In this study, we undertake a 5 years institutional review and analysis of OSCC cases in the south Indian setting. Results: The total number of the patients included 65 males (44.8%) and 80 females (55.2%) whose age ranged from 23 to 80 years (mean ± standard d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In this study, the mean age of the patients at presentation was 52.53 years. Study is comparable with study of Nayak et al [14] and Lekawale et al [15] From these studies, it is found that most of the SCCs of oral cancer patients present at fifth decade of age. In this study male-to-female ratio was 5:1, which is comparable with that in studies conducted by Iype et al [6] and Dewan et al [16] In this study, the incidence of SCC of the gingivobuccal complex was recorded to be maximum in businessmen (23.33%) followed by housewives and labourers (13.33% each).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the mean age of the patients at presentation was 52.53 years. Study is comparable with study of Nayak et al [14] and Lekawale et al [15] From these studies, it is found that most of the SCCs of oral cancer patients present at fifth decade of age. In this study male-to-female ratio was 5:1, which is comparable with that in studies conducted by Iype et al [6] and Dewan et al [16] In this study, the incidence of SCC of the gingivobuccal complex was recorded to be maximum in businessmen (23.33%) followed by housewives and labourers (13.33% each).…”
Section: Discussionsupporting
confidence: 90%